What did I look like when I was a baby? - Willis, Jeanne; Ross, Tony (New York : G.P. Putnam's, 2000)
A young boy and a series of animals learn that as babies, they looked like little versions of their mothers and fathers, but a young bullfrog is horrified when he is shown a photograph of himself as a tadpole.
2.8
K-3
K-3
School Library Journal
Publisher's Weekly
Booklist
Keywords: Animals -- Infancy -- Fiction; Frogs -- Fiction; Tadpoles -- Fiction; Parent and child -- Fiction; Self-perception -- Fiction; Animal babies -- Fiction; Frogs -- Fiction; Parent-child relationship -- Fiction; Self-perception -- Fiction